Evaluation of uncertainty of measurement of shadow mask dot pitch using different approaches. (April 2018) - Moona, Girija; Sharma, Rina; Kumar, Harish
The present paper discusses procedure for uncertainty of measurement evaluation in an experimental investigation to measure shadow mask dot pitch using laser interferometry. Here, we discuss evaluation of uncertainty of measurement in accordance to Law of propagation of uncertainties (GUM/LPU) and Monte Carlo Simulation (MCS) approaches. MCS has been recognized as an alternative approach to LPU in guide to measurement uncertainties (GUM) for evaluation of uncertainty of measurement and other related applications. A comparison of findings of GUM/LPU and MCS is made, which appears to be in good agreement. The present study attempts to investigate the suitability of MCS for evaluation of measurement of uncertainty in case of shadow mask dot pitch and reveals the significance of MCS in this regard.